Neoliberal Geopolitics, Indian Ocean and the Straits of Malacca. - Chaturvedi, Sanjay (2007)
What is currently unfolding in the international system is a neo-liberal geopolitics that pulls together various strands of realism and liberalism in ways hitherto considered unthinkable. One key example of this kind of formal geopolitical thinking is the work of Thomas P. Barnett, the author of the aptly titled The Pentagon’s New Map. It reflects a post-Cold War strategic mentality that has far reaching implications for India’s foreign policy. Offering unabashedly a pseudo-scientific justification for a corporate style of war making for regime change, and ‘democratisation’ of carefully selected sites on the globe, this neoliberal geopolitics provides an important context for critically examining the prospects for keeping the vital sea lanes of communication in the Indian Ocean open to all the stakeholders, including India.